Medical nutrition therapy in hospitalized patients with pemphigus vulgaris - Bintari Anindhita; Nurul Ratna Mutu Manikam (World Nutrition Journal, 2023)
Dysphagia due to involvement of the oral, pharyngolaryngeal, and esophageal mucosa and increased catabolism due to epidermal shedding can contribute to a decline in nutritional status in pemphigus vulgaris (PV) patients. On the other hand, decreased lean body mass is associated with immune system impairment, increased risk of infection, and delayed wound healing in PV patients, therefore, nutritional screening and assessment are necessary. Medical nutritional therapy in PV patients aims to overcome the metabolic response to the insults, prevent further malnutrition, modulate the immune system, and accelerate wound healing process. An aggressive nutritional support to minimize protein loss during the phase of mucocutaneous lesion healing is needed in patients with PV. Aside from macronutrient adequacy, micronutrients including vitamin A supplementation can be considered to accelerate wound healing process. Medical nutritional therapy including provision of adequate macronutrients, micronutrients, addressing dehydration and electrolyte imbalances should be the cornerstone of multidisciplinary treatment in PV patients.